Mercury exposure in the Norwegian Mother, Father, and Child Cohort Study – measured and predicted blood concentrations and associations with birth weight - Vejrup, Kristine; Brantsæter, Anne Lise; Caspersen, Ida H.; Haug, Line S.; Villanger, Gro D.; Aase, Heidi; Knutsen, Helle K. (Heliyon, 2024)
Blood total mercury concentration (BTHg) predominantly contains methyl Hg from seafood, and less inorganic Hg. Measured BTHg is often available only in a small proportion of large cohort study samples. Associations between estimated dietary intake of total Hg (THg) and lower birth weight within strata of maternal seafood intake was previously reported in the Norwegian Mother, Father, and Child Cohort Study (MoBa). However, maternal seafood consumption was associated with increased birth weight, indicating negative confounding by seafood in the association between THg intake and birth weight. Using predicted BTHg as a proxy for measured BTHg, we hypothesized that predicted BTHg would be associated with decreased birth weight. To develop and validate a prediction model for BTHg in MoBa and to examine the association between predicted BTHg and birth weight in the MoBa population. Using linear regression, measured maternal BTHg (n = 1437) was used to build the best fitting model (highest R-squared value). Model validation (n = 1436) was based on correlation and weighted Kappa (Кw). Associations between predicted BTHg in the MoBa population (n = 86,775) or measured BTHg (n = 3590) and birth weight were assessed by multivariate linear regression models. The best fitting model had R-squared = 0.3 and showed strong correlation (r = 0.53, p < 0.001) between predicted and measured BTHg. Cross-classification (quintiles) showed 73 % correctly classified and 3.3 % grossly misclassified, with Кw of 0.37. Measured BTHg was not associated with birth weight. Predicted BTHg was significantly associated with higher birth weight. There were no trends in birth weight with increasing quintiles of measured or predicted BTHg after stratification into high or low seafood consumption. The results indicate that prediction of BTHg did not overcome negative confounding of the association between Hg exposure and birth weight by seafood intake. Furthermore, effect on birth weight of toxicological concern is unexpected in our observed BTHg range. [Display omitted] •Model predicted blood total Hg was highly correlated with measured blood total Hg.•Measured blood total Hg (n = 3590) was not associated with birth weight.•Predicted blood total Hg (n = 86,775) was associated with higher birth weight.